Juridical analysis of the obstacles in the implementation of music royalty payment obligations in Indonesia - Ezra Natasya Br Simangunsong; Haposan Siallagan (Priviet Social Sciences Journal, 2025)
The main problem in this case study is that Indonesia still cannot be firm and fair in enforcing the obligation to pay music royalties to the composers. This already exists and is written in Law Number 28 of 2014 concerning copyright and in Government Regulation Number 56 of 2021. This refers to the consistency and compliance with the law that can be reviewed based on legal protection and legal compliance theory. This review will provide different perspectives on economic rights in song creation and how the intellectual property system applies. The review and normative juridical approach of this research provides an overview of the correct legal record and layout based on facts. This fact is based on literature studies, primary laws, and derivatives that can provide a more constructive research direction. This research provides an overview of the responsibility for a royalty and the importance of respecting intellectual property law. The challenge is the difficulty of making firm decisions by perpetrators or law enforcers due to the lack of transparency, which has become an inherent culture. Social socialization is very limited, and the absence of a national collective management institution provides certainty, making it difficult to run. The results of this study provide a conclusion that we must move together in echoing the synergy between LMKN, business actors, and the government in carrying out sustainable royalty management. This will strengthen the value of the existence of intellectual property rights and the emergence of legal certainty that can be claimed together for the sake of justice and social welfare in Indonesia.